Strategi Sosial Pencegahan Politik Uang di Indonesia - Kurniawan, Robi Cahyadi; Hermawan, Dedy (Komisi Pemberantasan Korupsi, 2019)
Money politics in elections and local elections is a phenomenon that is prevalent in procedural democracies in Indonesia, especially since the direct elections in 2004. Voters are very familiar with the term money politics and also do not hesitate to accept gifts in the form of money and goods. This paper tries to offer an effort to prevent the practice of money politics seen from the sociological and psychological aspects of voters, by providing an understanding of cognitive and affective aspects to instill in the minds of voters that money politics is a crime and a fundamental violation of ethics and morals. Voters in electoral practice can be influenced by their choices if they are given goods assistance or giving money. Relations or relationships between candidates and voters occur in terms of voting, providing services and personal activities, providing goods, providing projects, electoral fraud, identity appearance and raising funds for candidates for regional head candidates. The voter's social capital and local wisdom are expected to reduce the practice of money politics. Keywords: Social Capital, Local Wisdom, Money Politics